Temozolomide Followed by Combination With Low-Dose Ipilimumab and Nivolumab in Patients With Microsatellite-Stable, O6-Methylguanine–DNA Methyltransferase–Silenced Metastatic Colorectal Cancer: The MAYA Trial. Issue 14 (10th May 2022) - Morano, Federica; Raimondi, Alessandra; Pagani, Filippo; Lonardi, Sara; Salvatore, Lisa; Cremolini, Chiara; Murgioni, Sabina; Randon, Giovanni; Palermo, Federica; Antonuzzo, Lorenzo; Pella, Nicoletta; Racca, Patrizia; et al.
Abstract : PURPOSE: This is a multicenter, single-arm phase II trial evaluating the efficacy and safety of an immune-sensitizing strategy with temozolomide priming followed by a combination of low-dose ipilimumab and nivolumab in patients with microsatellite-stable (MSS) and O 6 -methylguanine–DNA methyltransferase (MGMT)–silenced metastatic colorectal cancer (mCRC). PATIENTS AND METHODS: Patients with pretreated mCRC were centrally prescreened for MSS status and MGMT silencing (ie, lack of MGMT expression by immunohistochemistry plus MGMT methylation by pyrosequencing). Eligible patients received two priming cycles of oral temozolomide 150 mg/sqm once daily, days 1-5, once every 4 weeks (first treatment part) followed, in absence of progression, by its combination with ipilimumab 1 mg/kg once every 8 weeks and nivolumab 480 mg once every 4 weeks (second treatment part). The primary end point was the 8-month progression-free survival (PFS) rate calculated from enrollment in patients who started the second treatment part, with ≥ 4 out of 27 subjects progression-free by the 8-month time point as decision rule. RESULTS: Among 716 prescreened patients, 204 (29%) were molecularly eligible and 135 started the first treatment part. Among these, 102 (76%) were discontinued because of death or disease progression on temozolomide priming, whereas 33 patients (24%) who achieved disease control started the second treatment part and represented the final study population. After a median follow-up of 23.1 months (interquartile range, 14.9-24.6 months), 8-month PFS rate was 36%. Median PFS and overall survival were 7.0 and 18.4 months, respectively, and overall response rate was 45%. Grade 3-4 immune-related adverse events were skin rash (6%), colitis (3%), and hypophysitis (3%). No unexpected adverse events or treatment-related deaths were reported. CONCLUSION: The MAYA study provided proof-of-concept that a sequence of temozolomide priming followed by a combination of low-dose ipilimumab and nivolumab may induce durable clinical benefit in MSS and MGMT-silenced mCRC. Abstract :